2015
DOI: 10.4254/wjh.v7.i15.1921
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and substance use disorders co-morbidities and hepatitis C: Diagnostic and treatment implications

Abstract: Chronic hepatitis C virus (HCV) viral infection is the most common blood-borne viral infection and approximately 2%-3% of the world's population or 170-200 million people are infected. In the United States as many as 3-5 million people may have HCV. Psychiatric and substance use disorders (SUDs) are common co-morbid conditions found in people with HCV and are factors in predisposing people to HCV infection. Also, these co-morbidities are reasons that clinicians exclude people from antiviral therapy in spite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 96 publications
1
16
0
Order By: Relevance
“…Adherence among patients with chronic HCV infection and comorbid psychiatric disorders remains a concern despite the advent of IFN‐free DAA treatments. Lower adherence is hypothesized due to cases of severe, untreated psychiatric disorders and higher rates of comorbid substance use disorders ; however, DAA regimens have shown similarly high adherence rates in clinical trials among patient populations traditionally considered to be at‐risk for nonadherence including patients with psychiatric disorders, people who inject drugs and patients on stable opioid substitution therapy . In its clinical trial programme, overall adherence to G/P regimens has been reported at >95% with comparable rates among patients with psychiatric disorders, people who inject drugs and patients on stable opioid substitution therapy .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adherence among patients with chronic HCV infection and comorbid psychiatric disorders remains a concern despite the advent of IFN‐free DAA treatments. Lower adherence is hypothesized due to cases of severe, untreated psychiatric disorders and higher rates of comorbid substance use disorders ; however, DAA regimens have shown similarly high adherence rates in clinical trials among patient populations traditionally considered to be at‐risk for nonadherence including patients with psychiatric disorders, people who inject drugs and patients on stable opioid substitution therapy . In its clinical trial programme, overall adherence to G/P regimens has been reported at >95% with comparable rates among patients with psychiatric disorders, people who inject drugs and patients on stable opioid substitution therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hepatitis C virus infection is associated with neuropsychiatric disorders in up to 50% of cases . Historically, patients with comorbid psychiatric disorders were less likely to receive HCV treatment since interferon (IFN)‐based regimens can induce depression and other neuropsychiatric manifestations including insomnia, irritability and mood changes . Treatment adherence among this patient population was also a concern due to IFN's psychiatric side effect profile and perceived risks of lower adherence in patients with psychiatric and/or substance use disorders .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also critical to note the implications of utilizing newer antiviral drugs in the context of HCV and common comorbidities. The development of new medications, including direct acting antiviral agents (DAA) that are used to treat HCV has allowed providers to treat people who have or are at risk for pain, depression, and SUD and otherwise would have been excluded from antiviral treatment [133]. Telaprevir, simeprevir and sofosbuvir in combination with IFN therapy can significantly decrease treatment duration without exacerbating side effects of interferon therapy, such as depressive symptomatology and muscle aches.…”
Section: Implications For Assessment and Treatmentmentioning
confidence: 99%